Study of changing trends and patterns in maternal mortality at a tertiary care hospital - Lokapur, Jyoti G.; C. Antaratani, Ramalingappa; Lokapur, Mallikarjun G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Maternal mortality continues to be a critical indicator of healthcare quality and socioeconomic development, particularly in developing nations. This study analyzes the evolving trends and patterns of maternal deaths at Karnataka institute of medical sciences (KIMS), Hubli, a major tertiary care center serving multiple districts in North Karnataka. Methods: This cross-sectional observational study combined retrospective and prospective approaches to analyze maternal deaths at the department of obstetrics and gynecology, KIMS, Hubli, from 2019 to 2023. Medical records were reviewed for all maternal deaths occurring within 42 days of pregnancy termination, including complications from pregnancy, labor, puerperium, and related interventions. Data analysis encompassed maternal age, parity, antenatal registration, delivery characteristics, admission-to-death interval, and cause of death. Statistical analysis was performed using proportions and means to establish patterns and correlations in the collected data. Results: A five-year analysis (2019-2023) at KIMS, Hubli documented 277 maternal deaths among 51,683 live births, yielding an average maternal mortality ratio (MMR) of 542.68 per 100,000 live births. The MMR peaked during 2021 (733.06) and subsequently declined to 437.46 in 2023. The majority of deaths occurred in women aged 20-25 years (53.79%) and primigravidas (57.03%), with hypertensive disorders (53.3%) being the leading direct cause of death. Notable trends included an increase in facility bookings (2.7% to 17.64%), a decrease in referred cases (100% to 70.5%), and a shift from vaginal deliveries (56.7% to 27.4%) to cesarean sections (32.4% to 52.9%). The COVID-19 pandemic’s impact was evident through increased indirect causes of death during 2020-2021, with pneumonia/COVID accounting for 36.4% of indirect deaths across the study period. Conclusions: The study revealed critical gaps in peripheral healthcare services and emphasized the need for strengthening antenatal care at primary healthcare centers. The high proportion of preventable causes highlights the importance of early detection, timely referral, and enhanced critical care capabilities in reducing maternal mortality.